2000
DOI: 10.1086/315828
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr Virus Gene Expression in the Peripheral Blood of Transplant Recipients with Persistent Circulating Virus Loads

Abstract: Pediatric solid organ transplant recipients are at risk for Epstein-Barr virus (EBV)-driven lymphoproliferative disease. The expression of 5 sentinel EBV genes (EBNA1, EBNA2a, LMP1, LMP2a, and ZEBRA) was examined in solid organ transplant recipients who developed persistent virus loads in their peripheral blood lymphocytes after transplantation. Two distinct groups were identified. LMP2a gene expression alone was detected among 12 of 14 patients carrying EBV loads < or =100 copies/10(5) lymphocytes. The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 33 publications
7
65
0
Order By: Relevance
“…This is based on studies of immunosuppressed organ transplant recipients who have high numbers of EBV-infected cells in the blood (31,33,(45)(46)(47) and are at risk for EBV lymphoproliferative diseases (48). In this study, we have shown that patients with SLE also have elevated frequencies of infected cells in the blood, similar to those seen in immunosuppressed organ transplant recipients (31).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This is based on studies of immunosuppressed organ transplant recipients who have high numbers of EBV-infected cells in the blood (31,33,(45)(46)(47) and are at risk for EBV lymphoproliferative diseases (48). In this study, we have shown that patients with SLE also have elevated frequencies of infected cells in the blood, similar to those seen in immunosuppressed organ transplant recipients (31).…”
Section: Discussionmentioning
confidence: 52%
“…Our laboratory and others (31,33,34) have shown previously that patients treated with immunosuppressive agents following organ transplant have high frequencies of EBV-infected cells in their blood. SLE patients are also treated with immunosuppressive drugs, albeit with fewer agents and at lower doses than patients who have received organ transplants.…”
Section: Treatment Of Sle Patients With Immunosuppressive Agents Doesmentioning
confidence: 90%
“…Therefore, the risk of developing PTLD continues for life, although early PTLD (in the first year after transplantation) occurs in cases of primary EBV infection [76]. On the otherhand asymptomatic EBV reactivation with high viral load is observed during the extended post-transplant follow-up [77]. The predictive value of the EBV load in solid organ transplantation is less clear, because some recipients have high EBV loads and remain stable for months or years without developing PTLD [78,79].…”
Section: Post-transplant Lymphoproliferative Disordermentioning
confidence: 99%
“…Additional information on viral gene expression would provide a better assessment of each patient's condition [39]. Qu et al examined the expression of EBV-associated genes in solid organ transplant recipients and found that persistent low-load carriers expressed only LMP-2, whereas high-load carriers expressed both LMP-1and LMP-2 [77]. They used qualitative reversetranscription PCR to detect EBV-associated genes.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, the determination of quantitative EBV genomic levels in peripheral blood may provide presumptive evidence for EBV involvement because EBVrelated complications are often associated with an increase in the circulating virus level. [13][14][15][16][17] It must be stressed that sensitivity and specificity of this assay have not yet been determined.…”
mentioning
confidence: 99%